1993
DOI: 10.1021/ma00064a009
|View full text |Cite
|
Sign up to set email alerts
|

Probing miscibility and intermolecular interactions in solid polymer blends using the nuclear Overhauser effect

Abstract: We discuss a new strategy for probing polymer-polymer miscibility and detecting specific intermolecular interactions in polymer blends by exploiting nuclear Overhauser effects (NOE) in 13C magicangle spinning (MAS) NMR spectra of solid blends. In the comparison of deuterated polystyrene (PS)/ poly(viny1 methyl ether) (PVME) blends cast from toluene versus chloroform, steady-state equilibrium NOE enhancements of the PS signals were observed for the toluene-cast films but not for the chloroform-cast films. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…This could be interpreted either as evidence for microphase separation or evidence that the component polymers have different dynamics in the miscible blend. Following these initial studies, several NMR experiments, including intermolecular cross polarization (19), NOE methods (20), and 2D multipulse exchange NMR (21), have shown that there are close contacts between the two chains. Other studies have shown that the blend contains heterogeneities on a length scale estimated to be 0.6 -3.5 nm (4,22).…”
Section: Discussionmentioning
confidence: 99%
“…This could be interpreted either as evidence for microphase separation or evidence that the component polymers have different dynamics in the miscible blend. Following these initial studies, several NMR experiments, including intermolecular cross polarization (19), NOE methods (20), and 2D multipulse exchange NMR (21), have shown that there are close contacts between the two chains. Other studies have shown that the blend contains heterogeneities on a length scale estimated to be 0.6 -3.5 nm (4,22).…”
Section: Discussionmentioning
confidence: 99%
“…Nemoto et al 2 calculated the diffusion coefficient and reported interaction between PS and PVME based on NMR analysis, 3,4 suggesting that the phenyl ring is much closer to the methyl group of PVME than to the main chain carbons of PS.…”
Section: F J Lu Et Al Reportedmentioning
confidence: 99%
“…[5][6][7][8] We recently developed a new solid-state NMR method to quantify chain dynamics in polymers with weak dynamic contrast: the NOE experiment with dipolar filter. [9] The principle of nuclear Overhauser effect (NOE) had been previously used differently in other solid-state NMR experiments to study miscibility in polymer blends [10][11][12] and chain dynamics in polymer melts, [13][14][15] or to differentiate chain length of branches in polyethylene. [16] The comparatively simple NOE experiment with dipolar filter is a combination of a conventional exchange experiment [4] with a dipolar filter, which selects according 28,160).…”
Section: Introductionmentioning
confidence: 99%